The contribution of the professional graduate of the Bachelor's degree and Bachelor's degree in Libraries and Documentation of the School of Libraries, Documentation and Information of the National University (Costa Rica), to the information society. - Meneses Hernández, Jorge (2007)
This research describes the contribution of the professional graduate School of Library, Documentation and Information of the National University of the Information Society.